2015
DOI: 10.1371/journal.pone.0124267
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Antimicrobial Products Used in Striped Catfish (Pangasianodon hypophthalmus) Aquaculture in Vietnam

Abstract: Antimicrobial usage is common in Asian aquaculture. This study aimed to determine the quality of antimicrobial products used by Vietnamese striped catfish (Pangasianodon hypophthalmus) farmers. Twenty one antimicrobial products (11 products contained a single antimicrobial and 10 products contained a mixture of two different antimicrobials) commonly used by catfish farmers were obtained from so-called chemical shops located in the Mekong Delta, Vietnam. Ultra High Performance Liquid Chromatography Mass Spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
2
18
1
1
Order By: Relevance
“…Our findings of substantial antimicrobial use in pig production are similar to those of Nguyen et al [10]. The use of higher antimicrobial dosages than recommended may be due to poor quality of the antimicrobials; a problem that has been documented for antimicrobials used in aquaculture in Vietnam [23]. Antimicrobial treatment of pigs until slaughter inevitably leads to accumulation of residues in pork products as documented by Hanh et al (2015), who found sulphadimidine residues in 50% and chloramphenicol residues in 17% of pork samples sold at wet markets in two Vietnamese provinces [24].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings of substantial antimicrobial use in pig production are similar to those of Nguyen et al [10]. The use of higher antimicrobial dosages than recommended may be due to poor quality of the antimicrobials; a problem that has been documented for antimicrobials used in aquaculture in Vietnam [23]. Antimicrobial treatment of pigs until slaughter inevitably leads to accumulation of residues in pork products as documented by Hanh et al (2015), who found sulphadimidine residues in 50% and chloramphenicol residues in 17% of pork samples sold at wet markets in two Vietnamese provinces [24].…”
Section: Resultssupporting
confidence: 85%
“…. The use of higher antimicrobial dosages than recommended may be due to poor quality of the antimicrobials; a problem that has been documented for antimicrobials used in aquaculture in Vietnam . Antimicrobial treatment of pigs until slaughter inevitably leads to accumulation of residues in pork products as documented by Hanh et al .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers in other Asian countries revealed similar concerns. Furthermore, Chinese substandard antimicrobial products may be sold to treat fish diseases in neighbouring countries, by both legal and illegal routes, which could cause treatment failure due to inferior quality of antimicrobial products (Chi, Clausen, Van, Tersbøl, & Dalsgaard, ; Phu, Phuong, Scippo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the product quality has been questioned; and inferior drug quality was suspected to be responsible for treatment failure and selection of bacteria carrying resistance genes in the external environment (Andersson & Hughes, ; Wang et al, ; Zhang, Ying, Pan, Liu, & Zhao, ). A recent study in Vietnam reported that conventional antimicrobial products used in striped catfish aquaculture had inferior quality with some not even containing the declared antimicrobials (Phu, Phuong, Scippo, & Dalsgaard, ), but the information of antimicrobial products in Chinese aquaculture is limited, as well as the instruction stated on the product label. Therefore, this study aimed to determine the quality of antimicrobial products commonly used in tilapia and shrimp aquaculture in China and to evaluate the instructions for use provided on product labels.…”
Section: Introductionmentioning
confidence: 99%
“…There is a concern that inadequate formulation of these products may lead to exposure to sub‐therapeutic levels of antimicrobials, therefore promoting resistance among bacterial populations (Nwokike, Clark, & Nguyen, ). Recent studies on the quality of antimicrobial products used in shrimp and catfish farming in Vietnam indicated that only ~8% and ~29% products contained an AAI within ±10% (accepted level of variation) (Phu, Phuong, Scippo, & Dalsgaard, ; Tran, Tran, Phan, & Dalsgaard, ). Globally, the quantity of antimicrobials used in chicken production is estimated at 138.0 doses/1,000 animal‐days [inter quartile range (IQR) 91.1–438.3], a higher amount than AMU in the two other major terrestrial food animal species (pig and cattle) (Cuong, Padungtod, Thwaites, & Carrique‐Mas, ).…”
Section: Introductionmentioning
confidence: 99%